Management in public administration: The decision anatomy x-rayed - Kulshrestha, N.K. (1994)
"The author makes a detailed presentation on the dynamics of decision making in the present Indian governmental setting at the individual executive level as well as the collective (committee) level underscoring the various factors which are responsible for the decision-making scenario. He then takes up for discussion the decision-making needs of future government, which he terms as `entrepreneurial decision making', keeping in view the vast changes in the nature of governance"
Keywords: Decision making - India; Public administration - India; Public administration